2015
DOI: 10.1159/000382018
|View full text |Cite
|
Sign up to set email alerts
|

Early Evolution of Human Respiratory Syncytial Virus ON1 Strains: Analysis of the Diversity in the C-Terminal Hypervariable Region of Glycoprotein Gene within the First 3.5 Years since Their Detection

Abstract: Objective: Characterization of the phylogeny and diversity of human respiratory syncytial virus (HRSV) genotype ON1 that occurred during its early evolution (within the first 3.5 years since the detection of the first ON1 strains). ON1 strains have a 72-nucleotide-long in-frame duplication within the second hypervariable domain of the glycoprotein gene (HVR2). Methods: All available HVR2 sequences of strains belonging to the ON1 genotype published prior to June 20, 2014 were collected. Multiple sequence alignm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…These results, based on locally collected data, are in contrast to those of our previous observation of similar diversities of globally detected ON1 and NA1 strains (calculated as the average number of base or amino acid differences per site) (Ivancic-Jelecki et al, 2015). Based on the substantially higher estimated substitution rate for ON1 than NA1 strains observed in this study, we expect that intra-ON1 and intra-NA1 p-distances for locally detected strains will follow the observed global trend in the near future.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results, based on locally collected data, are in contrast to those of our previous observation of similar diversities of globally detected ON1 and NA1 strains (calculated as the average number of base or amino acid differences per site) (Ivancic-Jelecki et al, 2015). Based on the substantially higher estimated substitution rate for ON1 than NA1 strains observed in this study, we expect that intra-ON1 and intra-NA1 p-distances for locally detected strains will follow the observed global trend in the near future.…”
Section: Discussioncontrasting
confidence: 99%
“…From the current epidemiological data, it seems that ON1 strains are even more successful in replacing NA1 strains (Kim et al, 2014;Pierangeli et al, 2014;Tabatabai et al, 2014). The reason for the epidemiological dominance of this genotype remains unknown, since there is no indication that ON1 strains cause more severe illness (Panayiotou et al, 2014;Ivancic-Jelecki et al, 2015). Our own unpublished data, in line with other reports from Europe (Panayiotou et al, 2014;Pierangeli et al, 2014;Tabatabai et al, 2014), indicate that ON1 is rapidly becoming the prevalent group A genotype.…”
Section: Discussionsupporting
confidence: 68%
“…This strain has a 60‐nucleotide in‐frame duplication within the second hypervariable domain of the glycoprotein (G) gene . Similarly, in December 2010, an HRSV‐A genotype named as ON1 was reported in Ontario, Canada; it has a 72‐nt‐long in‐frame duplication in the same domain of the G gene . The rapid dispersion of these genotypes was followed by their concurrent diversification, which has already generated 10 different BA variants …”
Section: Introductionmentioning
confidence: 97%
“…4,5 Phylogenetic studies of the second hypervariable region of the glycoprotein (G) gene identified 15 HRSV-A and 32 HRSV-B genotypes. 6,7 In 1999, an HRSV-B genotype named as BA was isolated in Buenos Aires, Argentina. This strain has a 60-nucleotide in-frame duplication within the second hypervariable domain of the glycoprotein (G) gene.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon resembles the BA genotype with a 60‐nucleotide duplication in the HVR2 of subgroup B [Trento et al, ]. Since its discovery, ON1 has spread globally and has been found mainly in Canada [Eshaghi et al, ], USA [Avadhanula et al, ], China [Cui et al, ], Korea [Kim et al, ], Japan [Tsukagoshi et al, ], Thailand [Auksornkitti et al, ], India [Choudhary et al, ], Malaysia [Khor et al, ], Germany [Prifert et al, ], Spain [Trento et al, ], Italy [Pierangeli et al, ], Latvia [Balmaks et al, ], Croatia [Ivancic‐Jelecki et al, ], Kenya [Agoti et al, ], Panama [Trento et al, ], Philippines, Peru, and South Africa [Pretorius et al, ]. The distribution together with global and local transmission dynamics of ON1 has also been reported recently [Duvvuri et al, ].…”
Section: Introductionmentioning
confidence: 99%